Assessment of the Effects of Digital Educational Material on Executive Function Performance - Lara Nieto-Márquez, Natalia; Cardeña Martínez, Alejandro; Baldominos, Alejandro; González Petronila, Almudena; Pérez Nieto, Miguel Ángel (Frontiers in Education, 2020)
The use of digital educational material in classrooms has increased in recent years, now constituting a major market for publishers and companies. The present research addresses a digital material assessment in two different areas. First, the study through an evaluation of internal data collected on the platform shows an analysis of the use and implementation of digital material into the school. Secondly, it exposes an external examination of the effect of using digital material at school on students’ executive functions. The sample consisted of 168 children aged 8-11 from a state school in the Community of Madrid (Spain). The instrument selected for the external assessment of academic progress was the Evaluación Neuropsicológica de las Funciones Ejecutivas en Niños (ENFEN) [Neuropsychological Assessment of Executive Functions in Children]. The Learning Analytics system of the Smile and Learn platform recorded the students’ use during class. According to the usage analysis, the results obtained show preference of using activities from Logic and Spatial worlds. In the external analysis of the effect of the learning material, the results record a significant effect using activities in Logic and Spatial worlds with the Grey Trails task, which involves spatial perception, processing speed and working memory, among others. A second analysis to contrast the results with a post hoc design approaches relationships among executive functions as involved in tasks like Grey Trails, Interference, and Ring Tasks within the usage of Spatial and Logic activities. The need for further research to improve these materials for enhanced learning, and the extrapolation of training from executive functions to other tasks is discussed. Likewise, limitations of the implementation and design of these materials are pointed out.